Modelação matemática : competência científica de uma licenciatura em matemática - Sostisso, Alessandra Fabian (2014)
This research aimed to identify the alphabetization and scientific competency in mathematical modeling of students in Mathematics in a Private University of Rio Grande do Sul. The methodological procedure was divided into four stages, called maps, namely: Identification Map - containing data and information supporting the choice of topic, objectives, subjects and methodological procedures that guided the research. Theoretical Map - are presented theories on Mathematical Modeling, Scientific Alphabetization and Competency Modeling in Education, and recent research that enabled this research to situate on a map of productions. Field Map - description of didactic implementation and organization of empirical data from activities with students in Mathematics. Analysis Map - carried out a qualitative study of the data from the categories of analysis able to apply mathematics - alphabetization; modeling how to do - competence. It was identified that students showed to have alphabetization and competency required in the perception and apprehension, but in the other stages of modeling, understanding and explanation, meaning and expression, showed difficulty in the skills required to formulate, solve and validate. It was found, also, the progress of students through the steps of modeling.